Working lives of maternity healthcare workers in Malawi: an ethnography to identify ways to improve careAJOG Global Reports at a Glance - Abi Merriel, PhD; Michael Larkin, PhD; Julia Hussein, MRCOG; Charles Makwenda, MSc; Address Malata, PhD; Arri Coomarasamy, MD (Elsevier, 2022)
BACKGROUND: Maternal mortality in East Africa is high with a maternal mortality rate of 428 per 100,000 live births. Malawi, whilst comparing favourably to East Africa as a whole, continues to have a high maternal mortality rate (349 per 100,000 live births) despite it being reduced by 53% since 2000. To make further improvements in maternal healthcare, initiatives must be carefully targeted and evaluated to achieve maximum influence. The Malawian Government is committed to improving maternal health; however, to achieve this goal, the quality of care must be high. Furthermore, such a goal requires enough staff with appropriate training. There are not enough midwives in Malawi; therefore, focusing on staff working lives has the potential to improve care and retain staff within the system. OBJECTIVE: This study aimed to identify ways in which working lives of maternity healthcare workers could be enhanced to improve clinical care. STUDY DESIGN: We conducted a 1-year ethnographic study of 3 district-level hospitals in Malawi. Data were collected through observations and discussions with staff and analyzed iteratively. The ethnography focused on the interrelationships among staff as these relationships seemed most important to working lives. The field jottings were transcribed into electronic documents and analyzed using NVivo. The findings were discussed and developed with the research team, participants, and other researchers and healthcare workers in Malawi. To understand the data, we developed a conceptual model, "the social order of the hospital," using Bourdieu's work on political sociology. The social order was composed of the social structure of the hospital (hierarchy), rules of the hospital (how staff in different staff groups behaved), and precedent (following the example of those before them). RESULTS: We used the social order to consider the different core areas that emerged from the data: processes, clinical care, relationships, and context. The Malawian system is underresourced with staff unable to provide high-quality care because of the lack of infrastructure and equipment. However, some processes hinder them on national and local level, for example staff rotations and poorly managed processes for labeling drugs. The staff are aware of the clinical care they should provide; however, they sometimes do not provide such care because they are working with the predefined system and they do not want to disrupt it. Within all of this, there are hierarchical relationships and a desire to move to the next level of the system to ensure a better life with more benefits and less direct clinical work. These elements interact to keep care at its most basic as disruption to the "usual" way of doing things is challenging and creates more work. CONCLUSION: To improve the working lives of the Malawian maternity staff, it is necessary to focus on improving the working culture, relationships, and environment. This may help the next generation of Malawian maternity staff to be happier at work and to better provide respectful, comprehensive, high-quality care to women.